Research conference summary from the 2014 International Task Force on ATP1A3-Related Disorders. (April 2017) - Rosewich, Hendrik; Sweney, Matthew T.; DeBrosse, Suzanne; Ess, Kevin; Ozelius, Laurie; Andermann, Eva; Andermann, Frederick; Andrasco, Gene; Belgrade, Alice; Brashear, Allison; Ciccodicola, Sharon; Egan, Lynn; et al.
Abstract : Objective: ATP1A3 -related neurologic disorders encompass a broad range of phenotypes that extend well beyond initial phenotypic criteria associated with alternating hemiplegia of childhood (AHC) and rapid-onset dystonia parkinsonism. Methods: In 2014, the Alternating Hemiplegia of Childhood Foundation hosted a multidisciplinary workshop intended to address fundamental challenges surrounding the diagnosis and management of individuals with ATP1A3 -related disorders. Results: Workshop attendees were charged with the following: (1) to achieve consensus on expanded diagnostic criteria to facilitate the identification of additional patients, intended to supplement existing syndrome-specific diagnostic paradigms; (2) to standardize definitions for the broad range of paroxysmal manifestations associated with AHC to disseminate to families; (3) to create clinical recommendations for common recurrent issues facing families and medical care providers; (4) to review data related to the death of individuals in the Alternating Hemiplegia of Childhood Foundation database to guide future efforts in identifying at-risk subjects and potential preventative measures; and (5) to identify critical gaps where we most need to focus national and international research efforts. Conclusions: This report summarizes recommendations of the workshop committee, highlighting the key phenotypic features to facilitate the diagnosis of possible ATP1A3 mutations, providing recommendations for genetic testing, and outlining initial acute management for common recurrent clinical conditions, including epilepsy.